1996
DOI: 10.1007/s002940050137
|View full text |Cite
|
Sign up to set email alerts
|

Isolation by genetic complementation of two differentially expressed genes for β-isopropylmalate dehydrogenase from Aspergillus niger

Abstract: We have constructed an Aspergillus niger cDNA library with a yeast expression vector. The library DNA complemented a leucine auxotroph of Saccharomyces cerevisiae (strain BWG1-7a) at a frequency of 4x10(-4). Plasmids rescued from the yeast prototrophs also complemented Escherichia coli (strain MC1066) deficient in leucine biosynthesis. Sequence determination of the rescued plasmids revealed two genes for beta-isopropylmalate dehydrogenase, which we called leu2A and leu2B. Genomic-blot analysis suggested that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Next, these first-screening positive clones were tested for the activation of the second reporter gene (lacZ) by their ability to generate blue colonies in the presence of X-gal. Library plasmids were extracted from positive yeast clones and separated from bait plasmids by transformation of the MC1066 E. coli strain [17]. These candidate plasmids were reintroduced into the Y190 yeast strain together with the original bait plasmid pGBT9-Bud32, or the pGBT9 plasmid alone, in order to confirm the interaction.…”
Section: Two-hybrid Screeningmentioning
confidence: 99%
“…Next, these first-screening positive clones were tested for the activation of the second reporter gene (lacZ) by their ability to generate blue colonies in the presence of X-gal. Library plasmids were extracted from positive yeast clones and separated from bait plasmids by transformation of the MC1066 E. coli strain [17]. These candidate plasmids were reintroduced into the Y190 yeast strain together with the original bait plasmid pGBT9-Bud32, or the pGBT9 plasmid alone, in order to confirm the interaction.…”
Section: Two-hybrid Screeningmentioning
confidence: 99%
“…cerevisiae , functional analysis showed that disruption of LEU2 resulted in Leu-auxotroph and decreased resistance to acetic acid and to very high levels of ethanol stress of the mutants [7]. Very few documents characterized functions of LEU2 in filamentous fungi except for a relatively ancient and primary research in Aspergillus niger showed that this fungus elaborates two isoenzymes of IPMD and these two encoding genes were differentially expressed [8]. However, the detailed function of these two paralogous LEU2 genes in Leu biosynthesis or other cellular processes was not investigated in A .…”
Section: Introductionmentioning
confidence: 99%
“…In total, ϳ7.0 ϫ 10 5 transformants were obtained, in which about 200 colonies grew on synthetic complete plates lacking tryptophan, leucine, and histidine (SC-Trp-Leu-His). As for the colonies, plasmids were recovered and transformed into an Escherichia coli strain MC1066 (29). Using the strain, the activation domain plasmids from the library were isolated by their ability to complement an E. coli leuB mutation as a result of the presence of the plasmid-borne LEU2 gene.…”
Section: Methodsmentioning
confidence: 99%